2020
DOI: 10.17219/acem/112058
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tau protein and Aβ42 level as markers of cognitive impairment in patients with Parkinson’s disease

Abstract: Background. Parkinson's disease (PD) is a progressive neurodegenerative disorder with a characteristic clinical picture. Apart from classical movement disorders, a significant role is also played by non-motor symptoms, in particular cognitive impairments, which have a significant impact on the quality of life of the patients. Tau protein and amyloid beta are well-known non-specific biomarkers in Alzheimer's disease (AD).Objectives. The study assessed the practical value of determining tau protein and amyloid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…A recent cross‐sectional study concluded no correlations between the levels of plasma Aβ42 and t‐tau and cognitive deficits in PD subjects, with variable plasma values detected 24 . In our study, a higher level of plasma t‐tau was associated with worse attention and executive function, although no significant correlations were found between plasma Aβ42 and any of the cognition domains.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A recent cross‐sectional study concluded no correlations between the levels of plasma Aβ42 and t‐tau and cognitive deficits in PD subjects, with variable plasma values detected 24 . In our study, a higher level of plasma t‐tau was associated with worse attention and executive function, although no significant correlations were found between plasma Aβ42 and any of the cognition domains.…”
Section: Discussioncontrasting
confidence: 72%
“…Limited studies investigated the relationships between the plasma values of Aβ and tau proteins and cognitive deficits in patients with PD. 10,24,25 Furthermore, studies to discuss the correlations between the plasma biomarkers and specific cognition domains in PD subjects are still lacking.…”
mentioning
confidence: 99%
“…On the one hand, overproduction or impaired elimination of Aβ can also occur in other diseases. Increased amyloid peptide concentrations were found in patients diagnosed with liver tumors [23], kidney [24] and liver [25] failure, Parkinson's disease [26], obesity and insulin resistance [27], or Down Syndrome [28]. On the other hand, a decrease in Aβ42 levels in the serum has been observed in depression [29].…”
Section: Amyloid Beta and Its Role In Dementia Processmentioning
confidence: 99%
“…Additionally, a lot of the biological processes and genes we found in our PD network has been implicated in the PD brain previously [11]. Tau and Aβ are hallmarks of both AD and PD in the brain and have potential as blood biomarkers in both diseases [50,51], suggesting that changes in the brain are reflected in blood.…”
Section: Discussionmentioning
confidence: 89%